Pengaruh Posisi Pronasi pada Bayi Prematur terhadap Perubahan Hemodinamik di NICU RS X - Ruth Herliana; Wilhelmus Hary Susilo; Tuti Asrianti Utami (Institut Nalanda, 2026)
The condition of premature babies is at risk of experiencing hemodynamic instability in terms of pulse, respiration and oxygen saturation. One of the actions taken to overcome the problem of hemodynamic instability in premature babies is to position the baby in a pronated position. The aim of the research was to analyze the effect of the pronation position in premature babies on hemodynamic changes in the NICU at Hospital. The results of the study found that the majority of male babies with SC delivery had an average gestational age of 34.17 weeks, an average birth weight of 1,867.57 grams and an average age of the baby 4.34 days. HR value (158.17 vs 147.48 145.20). RR (55.82 vs 48.57 vs 16.00). SpO2 (94.74 vs 100.0 vs 100.0). There is an influence of the pronation position on hemodynamic changes (HR, RR and SpO2) of premature babies before and after the pronation position is carried out in the NICU at Hospital It is hoped that nursing services can provide pronation as a complementary therapy that is appropriate, effective, safe and affordable for patients and easy to carry out by trained nurses so that it becomes one of the treatments that supports increasing HR, RR and SpO2 so that the implementation of the pronation position continues as an SOP in hospitals for premature and LBW babies.